Desenvolvimento rural desigual e combinado no espaço agrário cearense: elementos para a autonomia, subordinação ou exclusão da agricultura familiar camponesa nas áreas de assentamentos rurais - Lima, Maria Messias Ferreira (2020)
The contemporary debates about the destiny and especially the rural functions in the capitalism process expansion have influenced the public policies conduction for the sector. Such debates are eminently focused on proposing measures to reduce rural poverty without, however, contemplating an effective agrarian policy. In this sense, the permanence of peasant-based production units apparently has an infinite duality between capitalist mode and peasantry. In this context, the defended thesis in this research is which the rural territorial development policy implemented in Brazil between 2003 and 2014 came to create favorable conditions for the capital expanded reproduction and the expansion of capitalist relations in the countryside, creating elements which subordinate and / or exclude the peasant family farmer from the market dynamics, which is, from the process of capital production and accumulation, thus revealing their unequal and combined character. Thus, the research problem is to investigate the relations of Ceará agrarian space (re)production from the capital globalization under the aegis of rural development (DR), identifying the exclusion elements, subordination and autonomy of peasant family agriculture (AFC) to this process. The proposed study has as a geographical outline the territories of identity from the Ceará semiarid, and as object of investigation the federal rural settlements inserted in these territories, according to the administrative Division State. To choose the object of investigation, four criteria were considered: a) INCRA settlements consolidated; b) located in the semiarid; c) inserted in the project Territories of Citizenship and; d) underage. Considering the criteria defined for the determination of the study object, we obtained a population of 575 settled families. Through the calculation for stratified samples we reached a sample of 146 families, distributed in 06 (six) settlements. After collection, the data were tabulated and used to calculate the sustainable rural development index (IDRS). Given the character of the research, descriptive and explanatory, historical-dialectical materialism was the analysis method used to understand the productive forces organization process, considering them as determinants for the social space production in the field. In this context, the research made it possible to infer the following conclusion: the DTR policy was a factor of expansion of the capitalist production relations in the agrarian space, creating elements that first subordinate the peasant family farmer to the capitalist relations and, later, exclude them from the real possibilities for sustainable rural development. The originated elements reproduce the uneven logic and combined capital development